Precarização do entregador de alimento mediado por empresa de aplicativo - Macedo, Mariane Palhano (2024)
The precariousness of app-mediated food delivery in Brazil is evident and has intensified the country's inequalities during the pandemic. During the pandemic, these workers developed a movement with the purpose of improving working conditions, however, changes occurred slowly, and on the other hand, companies propagated information related to reality with the aim of manipulating young people able to work. , creating a utopia associated with this work. This study's main objective is to understand the precariousness of delivery drivers mediated by platform companies, who suffer various impacts on their work routine every day and how they are manipulated to enter and maintain the provision of services in these companies. The Covid-19 pandemic arrived in Brazil at a time when the country was already plagued by social inequalities and going through a phase of financialization of life under the neoliberal model, including the loss of social rights over the last few years. In this scenario, workers who were already in the informal market, unprotected and precarious, became pitiful, reaching a condition of exhaustion. Entrepreneurial work, while in reality this discourse of entrepreneurship is a form of manipulation and exploitation of workers. Companies convey an image of partnership and friendship with employees, however, workers are continually undervalued.